2014
DOI: 10.4067/s0034-98872014000200004
|View full text |Cite
|
Sign up to set email alerts
|

La edad de la mujer como factor de riesgo de mortalidad materna, fetal, neonatal e infantil

Abstract: Women age as a risk factor for maternal, fetal, neonatal and infant mortality (Rev Med Chile 2014; 142: 168-174)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
1
28

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 35 publications
5
8
1
28
Order By: Relevance
“…For example, the literature has reported that maternal age 6 , marital status 11 , lower level of education 7 , presence of hypertension or diabetes 9,10 and maternal obesity 8,19 are risk factors for neonatal death, which we could not be proved in our research.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…For example, the literature has reported that maternal age 6 , marital status 11 , lower level of education 7 , presence of hypertension or diabetes 9,10 and maternal obesity 8,19 are risk factors for neonatal death, which we could not be proved in our research.…”
Section: Discussioncontrasting
confidence: 51%
“…In Chile, it has been concluded that the main causes of neonatal death are congenital malformations, chromosomal abnormalities, prematurity and neonatal sepsis 4 . In addition, evidence suggests an association between increased risk of neaonatal death and maternal factors (directly or indirectly linked), such as: age 6 , low level of education 7 , obesity in pregnancy 8 , hypertension and diabetes 9,10 , as well as with social factors such as marital status and other socioeconomic variables 11,12 . Neonatal death is also associated with factors related to healthcare during pregnancy and childbirth, such as insufficient prenatal control and cesarean delivery 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Las razones de mortalidad a lo largo de la edad materna distribuyen en forma de J con aumento en los extremos de la vida acentuándose a medida que avanza la edad (2,3). Diferenciar los factores que contribuyen a esta distribución permite focalizar intervenciones en grupos de alto riesgo y promover los grupos de bajo riesgo.…”
Section: A Relevancia Clínica De La Investigaciónunclassified
“…No obstante, existen algunas apreciaciones en el contexto que devienen en estigma hacia ellos, en razón a si se unen, se encuentran en gestación o ejercen la crianza, pues en algunos casos se les asume como irresponsables y se considera que, por no haber llegado a la etapa adulta, no son aptos o eficaces para asumir este rol (14)(15)(16)(17)(18).…”
Section: Introductionunclassified